Thiabendazole and Thiabendazole-Formic Acid Solvate: A Computational, Crystallographic, Spectroscopic and Thermal Study - Tabanez, Andreia M. M. (2020)
Thiabendazole (TBZ) is a substance which has been receiving multiple important applications in several domains, from medicine and pharmaceutical sciences, to agriculture and food industry. Here, a comprehensive multi-technique investigation on the molecular and crystal properties of TBZ is reported. In addition, a new solvate of the compound is described and characterized structurally, vibrationally and thermochemically for the first time. Density functional theory (DFT) calculations were used to investigate the conformational space of thiabendazole (TBZ), revealing the existence of two conformers, the most stable planar trans form and a double-degenerated-by-symmetry gauche form, which is ~30 kJ mol-1 higher in energy than the trans conformer. The intramolecular interactions playing the major roles in determining the structure of the TBZ molecule and its conformational preferences were characterized. The UV-visible and infrared spectra of the isolated molecule (most stable trans conformer) were also calculated, and their assignment undertaken. The information obtained for the isolated molecule provided a strong basis for the understanding of the intermolecular interactions and properties of the crystalline compound. In particular, the infrared spectrum for the isolated molecule was compared with that of crystalline TBZ and the differences between the two spectra were interpreted in terms of the major intermolecular interactions existing in the solid state. The analysis of the infrared spectral data was complemented with vibrational results of up-to-date fully-periodic DFT calculations and Raman spectroscopic studies. The thermal behavior of TBZ was also investigated using differential scanning calorimetry (DSC) and thermogravimetry. Furthermore, a new TBZ-formic acid solvate [2-(1,3-thiazol-4-yl)benzimidazolium formate formic acid solvate] was synthesized and its crystal structure determined by X-ray diffraction. The Hirshfeld method was used to explore the intermolecular interactions in the crystal of the new TBZ solvate, comparing them with those present in the neat TBZ crystal. Raman spectroscopy and DSC studies were also carried out on the solvate to further characterize this species and investigate its temperature-induced desolvation.